Ts. Dr. Norashikin produces safe Aureiz brand personal care and hygiene products - Mimi Rabita, Abdul Wahit (2020)
Kuantan, 21 September 2020 - A lecturer from the Faculty of Chemical & Process Engineering Technology, Universiti Malaysia Pahang (UMP), Ts. Dr. Norashikin Mohd Zain, who has more than ten years of research experience at the university, has successfully produced three personal care and hygiene products from safe ingredients, namely antimicrobial hand wash, antimicrobial body cleanser and antimicrobial space cleaning spray.